(untitled) (Zdravstveni glasnik, 2024)
Introduction: Vaccination against infectious diseases is the most effective, cost-effective, often unavoidable, or the only possible way to protect individuals and the population from infectious diseases. In the last ten years, a lack of understanding and knowledge about the benefits of vaccination has led to a decline in the number of vaccinated children and the danger of the reappearance of already eradicated infectious diseases. Objective: To examine the knowledge and attitudes about mandatory vaccination of children among students of the Faculty of Health Studies and the Faculty of Medicine of the University of Mostar. Respondents and methods: A cross-sectional survey was conducted, which included 150 respondents in the third and fourth year of study, 50 respondents from the Faculty of Medicine, and 100 respondents from the Nursing and Sanitary Engineering study tracks at the Faculty of Health Studies. Data were collected through a self-assessment questionnaire. Results: Over 90% of respondents have a positive attitude towards vaccination and would vaccinate their children. The results show that respondents form their attitudes about vaccination based on academic activities. Students with a positive attitude about vaccination also showed greater knowledge about it. Nursing students have the weakest knowledge, followed by showing a greater aversion to vaccines than other respondents. More than a quarter of respondents are convinced of the connection between autism and vaccines, and this is also the case for autoimmune diseases. Conclusion: Although students of biomedical studies have positive attitudes about vaccination, the level of knowledge was more significant among students of the Faculty of Medicine compared to the study tracks of the Faculty of Health Studies.